A rare case of simple syndactyly in a puppy. (17th December 2013) - Macrì, F.; Ciotola, F.; Rapisarda, G.; Lanteri, G.; Albarella, S.; Aiudi, G.; Liotta, L.; Marino, F.
<x xml:space="preserve">Abstract</x> A case of non‐syndromic, complete syndactyly involving all four limbs is described in a three‐month‐old male crossbreed dog for the first time. Syndactyly is a rare condition in most animal species, in dogs it has been infrequently reported. Findings of clinical, radiographic and cytogenetic analyses are described and demonstrate probably for the first time that numerical and structural chromosome aberrations are not involved in the pathogenesis of this case of syndactyly.